A Novel Strategy for Umbilical Granuloma Removal: Cutting off with a Nylon Suture Thread - Taniguchi, Kazuto; Mizuta, Kazutaka; Uemichi, Kazuyasu (Journal of Nepal Paediatric Society, 2022)
Umbilical granuloma is a common umbilical problem in infants. Although various modalities are available for the treatment of umbilical granulomas, the best method remains controversial. A 7-week-old infant presented with umbilical granuloma followed by omphalitis. We treated the omphalitis first to prevent local inflammation. On the following day, the umbilical granuloma was successfully cut off with a nylon suture thread. No residue of the granuloma was left behind and no signs of local inflammation appeared. Umbilical granuloma can be successfully removed with a nylon suture thread. Treatment for omphalitis before granuloma removal may be useful to prevent local inflammation.